Application Studies of Li-ion Battery in Railway Passenger-cars - 苑丰彪; 杨君 (机车电传动)
Power supply system and parameters of railway passenger-cars were analyzed. Performances of three types of batteries were compared and the advantages of Li-ion battery were indicated. Moreover, application schemes of Li-ion battery for railway passengercars power supply system were studied and discussed.